Pengaruh Pengelolaan Aset Desa, Optimalisasi Pemanfaatan BUMDes dan Kinerja Pemerintah Desa Terhadap PADes Desa Wonorejo - Sabili Nur Aini; Setyaningsih Sri Utami (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to prove the influence of Village Asset Management, Optimizing the Utilization of Village-Owned Enterprises, and Village Government Performance on Village Original Income in Wonorejo Village, Gondangrejo District, Karanganyar Regency. This research uses quantitative data with the data source, namely primary data obtained directly from the research object. The population in this study was 31 respondents, namely the village government, administrators of Village-Owned Enterprises, kiosk/building tenants, and village treasury land tenants. The sampling technique uses non-probability sampling with a sampling technique, namely saturated sampling. Data collection techniques use questionnaires, observation, interviews and literature study. Data analysis techniques use multiple linear regression, t test, F test, and R2 test. The results of this research show that managing Village Assets, Optimizing the Utilization of Village-Owned Enterprises, and the Performance of the Village Government have an significant effect on the Village's Original Income in Wonorejo Village, Gondangrejo District, Karanganyar Regency. The calculated F test result is 42.704 with a significance value (p-value) of 0.000 <0.05, which indicates that the independent variable together they influence the dependent variable. The coefficient of determination test result (R2) is 0.807, which means the contribution of the influence of the independent variable is 80.7%. The remainder (100%-80,7%=19,3%) is explained by other variabels outside the model